Associations between GoSmart Channel, health literacy and health behaviours in adolescents: A population‐based study - Junjie Huang; Sze Chai Chan; Vera M. W. Keung; Calvin K. M. Cheung; Amelia S. C. Lo; Vincent T. C. Lau; Lancelot W. H. Mui; Albert Lee; Martin C. S. Wong (Wiley, 2024)
Abstract Background Health literacy is essential in the promotion of healthy lifestyle habits and chronic disease prevention. Objective To assess the health literacy level among Hong Kong adolescents; to evaluate the association between access of an online health information platform (GoSmart Channel) and health literacy level; and to examine the association between health literacy level and various unhealthy behaviours. Design This study recruited students from 10 local secondary schools in Hong Kong to assess the health literacy level among adolescents. Settings and Participants Participants were required to complete a self‐administered questionnaire on health behaviours and health literacy using the Health Literacy Measure for Adolescents (HELMA). Main Outcome Measure Data were analysed using descriptive statistics and multivariate regression modelling. Results A total of 777 responses were collected. Overall, most (74.4%) of the adolescents in Hong Kong have limited health literacy (HELMA score <66). The majority (63.7%) of adolescents relied on their parents for health information, while 11.4% of the respondents sought information from the GoSmart Channel. The intervention of GoSmart Channel was significantly associated with better health literacy in almost all aspects among adolescents. Desired levels of health literacy were significantly associated with better perceived health (adjusted odds ratio: 2.04, p = .001) and negatively associated with a range of unhealthy and risky behaviours including unhealthy dietary habits, poor hygienic measures and physical inactivity. Discussion and Conclusion This study highlights the importance of improving health literacy among Hong Kong adolescents and the potential of technology‐based interventions. The findings suggest the need for continued efforts to promote health literacy and healthy behaviours among adolescents, especially given the limited health literacy levels observed in the study. Patient or Public Contribution Members of the GoSmart.Net Built‐on Project patient and public involvement and engagement group advised about survey development.